Does narcissism moderate training on performance among millennial and gen z accountants at startups? - Sari Lestari; Siti Mutmainah (Cogent Business & Management, 2023)
Understanding the performance of millennial and Gen Z accountants in start-ups is compelling due to their role in enhancing start-up resilience. While training can improve employee performance, concerns arise about the impact of narcissistic personalities. The research aims to uncover the narcissistic personalities of millennial and gen z accountants by moderating the effect of training on their performance. The research used quantitative methods. Data collection through questionnaires. The study involved 100 respondents obtained using purposive sampling techniques. The data were analyzed using moderated regression analysis with SPSS. The results of the research showed that training had a positive impact on the performance of millennial and gen z accountants working in start-ups. Narcissism does not exhibit significant moderation of the training effect on accounting performance at the 5% level; however, it becomes noteworthy at the 10% level and has a positive influence. These findings have implications for the study of accounting, especially in the fields of business and management. The research emphasizes the importance of training programs to improve the performance of millennial and gen z accountants in the start-up environment. The non-moderate effect of narcissistic personalities contributes to organizations not worrying too much about the effects of narcissistic personalities on training. Focusing on training as the development of wider competences is more meaningful. This research has its limitations; it only involves accountants who practice in the private sector. Further research could develop for subjects in other work environments, such as public accountants, government accountants, or even educational accountants.
Keywords: 650; accountant performance; millennial and gen z accountant; narcissism; start-up; training